Asymptotics of solutions of a hyperbolic formulation of the constraint equations. (27th September 2017) - Beyer, F; Escobar, L; Frauendiener, J
Abstract: In this paper we consider the hyperbolic formulation of the constraints introduced by Rácz. Using the numerical framework recently developed by us we construct initial data sets which can be interpreted as nonlinear perturbations of Schwarzschild data in Kerr–Schild coordinates and investigate their asymptotics. Our results suggest that, unless one finds a way to exploit the freedom to pick the free part of the initial data in some suitable way, generic initial data sets obtained by this method may violate fundamental asymptotic conditions.